2020
DOI: 10.1111/jcmm.15812
|View full text |Cite
|
Sign up to set email alerts
|

A biflavonoid‐rich extract from Selaginella moellendorffii Hieron. induces apoptosis via STAT3 and Akt/NF‐κB signalling pathways in laryngeal carcinoma

Abstract: Laryngeal cancer is a common invasive malignant tumour of the head and neck, and an important cause of morbidity and mortality worldwide. 1 It accounts for 5.7% to 7.6% of systemic malignant tumours. 2 More than 150,000 new cases of laryngeal cancer are diagnosed each year, 3 and its incidence is increasing. 4 Current treatment methods mainly include surgery, chemotherapy, radiation therapy, and biological therapy, and sometimes a combination of these. 5 Although these comprehensive treatments have improved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Hep-2 cells in the logarithmic phase of apposed growth were inoculated with 2 × 10 5 cells in 6-well cell culture plates, and the cells were fused to approximately 80% of the total number of cells (Huang et al., 2020 ). After respectively treatment with Free PTX, mPEG-CS/PTX, mPEG-CS-cRGD/PTX and mPEG-CS-cRGD/ Bmi-1RNAi -PTX (the final concentration of PTX was the IC 50 of Hep-2 cells of 90.11 ng/mL), the surface of the plate was scratched with a 200 μL sterile pipette tip to form a trabecular surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hep-2 cells in the logarithmic phase of apposed growth were inoculated with 2 × 10 5 cells in 6-well cell culture plates, and the cells were fused to approximately 80% of the total number of cells (Huang et al., 2020 ). After respectively treatment with Free PTX, mPEG-CS/PTX, mPEG-CS-cRGD/PTX and mPEG-CS-cRGD/ Bmi-1RNAi -PTX (the final concentration of PTX was the IC 50 of Hep-2 cells of 90.11 ng/mL), the surface of the plate was scratched with a 200 μL sterile pipette tip to form a trabecular surface.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were fixed in 4% paraformaldehyde, dehydrated, permeabilised and embedded, then cut into 5 um sections, incubated overnight with the primary antibody used for the experiments. Combined with the analogous horseradish peroxidase, finally stained, sealed, photographed under 200x in a positive microscope (Leica) and the positive staining ratio quantified using ImageJ software (Hua et al., 2018 ; Huang et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The extract suppressed the migration of laryngeal cancer cells, via an induction of apoptosis and inhibition of STAT3 and the Akt/NFκB signaling pathway. Importantly, the extract showed a dose-dependent activity in vivo, reducing the subcutaneous growth of Hep-2 tumor in mice [ 46 ]. HNK is one of the many active compounds that can be found in this type of extract [ 47 ].…”
Section: Anticancer Activity Of Hnk-containing Plant Extractsmentioning
confidence: 99%
“…4). Recently, a noticeable anticancer effect was reported using a purified extract of another Selaginella specie, namely Selaginella moellendorffii Hieron which was found to contain mainly six biflavonoids including HNK [46]. The extract suppressed the migration of laryngeal cancer cells, via an induction of apoptosis and inhibition of STAT3 and the Akt/NFκB signaling pathway.…”
Section: Anticancer Activity Of Hnk-containing Plant Extractsmentioning
confidence: 99%
“…It is mainly used as an ascaris repellent; additionally, it has biological activities including anti-botulism, neuromuscular junction inhibition, and central nervous and respiratory system effects [7]. A large number of studies have shown the efficacy of natural products in cancer treatment, particularly, in cancer drug research [8][9][10]. Among them, TSN has recently been shown to possess anti-tumor activity in many tumor cells including gastric, lung, pancreatic, colorectal, liver, and breast cancer cells [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%